Composite cleaning agent containing functional polymer anti-redeposition agent and method for preparing the same
Patent Information
- Application Number
- CN202611025659.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于提供含功能高分子抗再沉积剂的复合清洁剂及其制备方法,用于解决在现有技术中的复合清洁剂去污性能和抗再沉积性能有待进一步提高的技术问题
在复合清洁剂体系中,十二烷基苯磺酸钠作为主体表面活性组分,通过水相中的润湿和乳化作用实现对织物表面污物的初步渗透与分散,与其配伍的协同增溶剂在水相中形成连续分散通道,使活性组分能够在纤维表面均匀分布,减少局部浓集,且引入的核壳抗再沉积剂,其由两性接枝聚合体作为壳层、环氧硅稳定微胶粒作为核组成,可在颗粒表面形成微观保护层,使已脱离的污物保持分散,降低再次附着的趋势,配合柠檬酸三钠二水合物与碳酸钠对液相环境的调节,体系中各组分在初期接触与后续作用阶段形成顺畅过渡,使纤维表面活性覆盖状态均匀,整体呈现整洁、均匀的外观状态。
Smart Images

Figure CN122879022A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cleaning agent preparation, specifically to a composite cleaning agent containing a functional polymeric anti-redeposition agent and its preparation method. Background Technology
[0002] Fabric cleaning agents typically consist of multiple components such as surfactants, builders, chelating agents, enzymes, optical brighteners, and fragrances to meet the comprehensive requirements of daily washing for stain removal, dispersion, whitening, and stability. To reduce the re-adhesion of dirt particles onto the fabric surface during washing, anti-redeposition agents are often added. The main materials include carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylate, and other water-soluble functional polymers. The above technologies have been widely used in laundry detergents, fabric care agents, and other household cleaning products.
[0003] However, in practical applications, although traditional compound detergents can remove and transfer dirt, the dirt particles often need to remain in a stable dispersed state in the washing liquid after being removed from the fabric surface in order to reduce re-contact and re-attachment. For systems containing sebum, particulate dust and complex stains, conventional anti-redeposition components are often insufficient in terms of liquid phase maintenance and interface isolation, which makes it easy for the removed dirt particles to aggregate or re-attach to the fabric surface during rinsing and mechanical agitation, thereby affecting the post-wash appearance, whiteness retention and the consistency of the overall washing effect.
[0004] In addition, traditional functional polymeric anti-redeposition agents are mostly single linear water-soluble polymers, and their mode of action in composite detergents is relatively simple. When the system contains multiple surface-active components, inorganic salts or whitening components, problems such as insufficient compatibility, uneven distribution or insufficient linkage of actions often occur. On the one hand, some components are prone to competitive adsorption or local aggregation, which affects the migration and spread of effective ingredients in the aqueous phase. On the other hand, there is a lack of continuous synergy between the anti-redeposition effect and the front-end detergency action, making it difficult for composite detergents to achieve a better overall balance between detergency, dispersion and inhibition of redeposition. Summary of the Invention
[0005] The purpose of this invention is to provide a composite cleaning agent containing a functional polymer anti-redeposition agent and its preparation method, in order to solve the technical problem that the detergency and anti-redeposition properties of composite cleaning agents in the prior art need to be further improved.
[0006] The objective of this invention can be achieved through the following technical solution: a composite cleaning agent containing a functional polymer anti-redeposition agent, comprising the following raw material components by weight: 170-190 parts sodium dodecylbenzenesulfonate, 110-130 parts trisodium citrate dihydrate, 70-90 parts sodium carbonate, 4-6 parts sodium benzoate, 32-38 parts synergistic solubilizer, and 23-27 parts core-shell anti-redeposition agent; The synergistic solubilizer is a complex polymer dispersion composed of cyclodextrin, alkyl glycoside and polycarboxylate; The core-shell anti-redeposition agent is a core-shell type functional polymer dispersion composed of an epoxy-siloxane lignin hybrid core and a hydroxyethyl cellulose grafted amphoteric polycarboxylate shell.
[0007] Furthermore, the preparation method of the core-shell anti-redeposition agent is as follows: deionized water, anhydrous ethanol and epoxy silicon stabilized microparticles are added to a reaction vessel and stirred and dispersed. After stirring evenly, amphoteric graft polymer is added, followed by sodium carbonate. The reaction vessel is heated to 72-78℃ and stirred for 4.5-5.5 hours. The core-shell anti-redeposition agent is then obtained through post-treatment.
[0008] Furthermore, the ratio of deionized water, anhydrous ethanol, epoxy silicone stabilized microparticles, amphoteric graft polymer, and sodium carbonate is 110-230mL:25-35mL:6-9g:13-16g:1.1-1.4g. The post-treatment includes: removing the solvent under reduced pressure after the reaction, drying the obtained material in a vacuum drying oven at 45-55℃ for 8-10 hours, and pulverizing it through a 100-120 mesh sieve to obtain the core-shell anti-redeposition agent.
[0009] Furthermore, the preparation method of the amphoteric graft polymer is as follows: deionized water and hydroxyethyl cellulose are added to a reaction vessel and stirred to swell. After stirring evenly, acrylic acid is added, followed by 50wt% sodium hydroxide solution and 60wt% diallyldimethylammonium chloride aqueous solution. After stirring evenly, nitrogen gas is introduced, followed by 5wt% ammonium persulfate aqueous solution and 3wt% sodium bisulfite aqueous solution. The reaction vessel is heated to 63-68℃ and stirred for 4-5 hours. The amphoteric graft polymer is obtained after post-treatment.
[0010] Furthermore, the ratio of deionized water, hydroxyethyl cellulose, acrylic acid, 50wt% sodium hydroxide solution, 60wt% diallyl dimethyl ammonium chloride aqueous solution, 5wt% ammonium persulfate aqueous solution, and 3wt% sodium bisulfite aqueous solution is 125-150mL:11-14g:8-10mL:3-4mL:11-14mL:8-9mL:5-7mL. The post-treatment includes: after the reaction, adjusting the system to pH=6.5-7.5 with 10wt% sodium hydroxide solution, then adding three times the volume of anhydrous ethanol to precipitate, filtering to collect the filter cake, washing 2-3 times with 70wt% ethanol aqueous solution, drying the filter cake in a vacuum drying oven at 45-55℃ for 10-12h, pulverizing and passing it through an 80-100 mesh sieve to obtain the amphoteric graft polymer.
[0011] Furthermore, the preparation method of the epoxy silicon stabilized microparticles is as follows: anhydrous ethanol, deionized water and lignin are added to a reaction vessel and stirred and dispersed. After stirring evenly, 25wt% ammonia water is added, followed by 3-glycidyl etheroxypropyltrimethoxysilane and tetraethyl orthosilicate. The reaction vessel is heated to 38-42℃ and stirred for 3.5-4.5h. Then, the temperature is raised to 48-52℃ and matured for 7-9h. The epoxy silicon stabilized microparticles are obtained after post-treatment.
[0012] Furthermore, the ratio of anhydrous ethanol, deionized water, lignin, 25wt% ammonia, 3-glycidyl etheroxypropyltrimethoxysilane, and tetraethyl orthosilicate is 160-200mL:45-65mL:18-22g:4-6mL:16-20mL:18-22mL. The post-treatment includes: centrifugation after the reaction, washing with 70wt% ethanol aqueous solution 2-3 times and deionized water 1-2 times, drying the obtained solid in a vacuum drying oven at 55-65℃ for 8-10h, pulverizing and passing it through an 80-mesh sieve to obtain epoxy silicon stabilized microparticles.
[0013] Furthermore, the preparation method of the synergistic solubilizer is as follows: deionized water and hydroxypropyl-β-cyclodextrin are added to a reaction vessel and stirred to dissolve. After stirring evenly, decyl glucoside is added, followed by sodium gluconate. The reaction vessel is heated to 40-50℃ and stirred for 1-2 hours. The synergistic solubilizer is then obtained through post-treatment.
[0014] Furthermore, the ratio of deionized water, hydroxypropyl-β-cyclodextrin, decyl glucoside, and sodium gluconate is 120-150 mL: 27-33 g: 16-20 mL: 13-17 g. The post-treatment includes: concentrating under reduced pressure to a solid content of 65-75 wt% after the reaction, drying the concentrate in a vacuum drying oven at 40-50°C for 8-10 hours, and pulverizing it through an 80-100 mesh sieve to obtain a synergistic solubilizer.
[0015] The present invention also discloses a method for preparing a composite cleaning agent containing a functional polymer anti-redeposition agent, comprising the following steps: adding sodium dodecylbenzenesulfonate, trisodium citrate dihydrate, sodium carbonate and sodium benzoate into a mixer for premixing, stirring evenly, adding a synergistic solubilizer, adding a core-shell anti-redeposition agent, continuing to stir and mix, granulating through a 40-60 mesh sieve after mixing, sealing and packaging to obtain the composite cleaning agent.
[0016] Further post-processing includes: granulation through a 40-60 mesh sieve after mixing, sealing and packaging to obtain the composite cleaning agent.
[0017] The present invention has the following beneficial effects: In the composite cleaning agent system, sodium dodecylbenzenesulfonate serves as the main surfactant component. Through wetting and emulsification in the aqueous phase, it achieves initial penetration and dispersion of dirt on the fabric surface. The synergistic solubilizer it is paired with forms a continuous dispersion channel in the aqueous phase, allowing the active component to be evenly distributed on the fiber surface and reducing local concentration. The introduced core-shell anti-redeposition agent, composed of amphoteric graft polymers as the shell and epoxy silica-stabilized microparticles as the core, can form a microscopic protective layer on the particle surface, keeping the detached dirt dispersed and reducing the tendency for re-attachment. Combined with the regulation of the liquid phase environment by trisodium citrate dihydrate and sodium carbonate, the components in the system form a smooth transition between the initial contact and subsequent action stages, resulting in a uniform surface active coverage on the fibers and an overall clean and uniform appearance. During system operation, the core-shell anti-redeposition agent plays a crucial role in maintaining the dispersion of particles in the liquid phase. Its outer hydrophilic structure is in full contact with the aqueous phase, while the core protects the detached dirt particles, making them less prone to aggregation in the liquid phase. At the same time, sodium dodecylbenzenesulfonate and synergistic solubilizers optimize the liquid phase dispersion network, making the distribution of each active component in the system more uniform and avoiding local enrichment. Trisodium citrate dihydrate and sodium carbonate regulate the pH and ionic strength of the aqueous phase, stabilizing the suspension state of the particles in the liquid phase and delaying the sedimentation trend. Thus, the system maintains continuous cooperation throughout the entire process from dirt detachment to liquid phase distribution. The contact opportunities between dirt particles and fiber surfaces are relatively limited, and the role of active components in the system exhibits a relatively balanced continuity and coordination. After the composite detergent comes into contact with the aqueous phase, the synergistic solubilizer composed of hydroxypropyl-β-cyclodextrin, decyl glucoside, and sodium gluconate rapidly establishes hydration channels, enabling sodium dodecylbenzenesulfonate and trisodium citrate dihydrate to enter an effective state within a short time. At the same time, the core-shell anti-redeposition agent maintains uniform dispersion of liquid phase particles through its core-shell structure, preventing local sedimentation or aggregation, and ensuring that the release rhythm of each functional component is coordinated. Sodium carbonate and sodium benzoate provide support for the stability of the system, enabling a smooth transition between the initial dissolution, dispersion, and subsequent action. The synergistic unfolding of multiple components in the aqueous phase allows the detergent to maintain a balanced and continuous action state during use. The release and distribution of different functional components can cooperate with each other to maintain the consistency of the overall system. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a SEM image of the core-shell anti-redeposition agent prepared in Example 3 of the present invention; Figure 2 This is a SEM image of the synergistic solubilizer prepared in Example 6 of the present invention. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] In this application, the degree of molar substitution of hydroxyethyl cellulose (MS) is 1.95-2.05, and its 2wt% aqueous solution has a viscosity of 320-360 mPa·s at 25°C; the lignin used is alkali lignin with a weight-average molecular weight of 1800-2100 and a purity of 93-94wt%. Example
[0022] This embodiment provides a method for preparing a core-shell anti-redeposition agent, including the following steps: Step I: Preparation of amphoteric grafted polymers Weigh out 125.0 mL of deionized water and 11.0 g of hydroxyethyl cellulose and add them to the reaction vessel. Stir until swollen and homogeneous. Add 8.0 mL of acrylic acid, then add 3.0 mL of 50 wt% sodium hydroxide solution and 11.0 mL of 60 wt% diallyl dimethyl ammonium chloride aqueous solution. Continue stirring until homogeneous and then purge with nitrogen gas. Add 8.0 mL of 5 wt% ammonium persulfate aqueous solution and 5.0 mL of 3 wt% sodium bisulfite aqueous solution. Heat the reaction vessel to 63 °C and stir for 4 h. After the reaction is complete, adjust the pH of the system to 6.5 with 10 wt% sodium hydroxide solution. Add three times the volume of anhydrous ethanol to precipitate the mixture. Filter and collect the filter cake. Wash twice with 70 wt% ethanol aqueous solution. Place the filter cake in a vacuum drying oven at 45 °C and dry for 10 h. Crush and pass through an 80-mesh sieve to obtain the amphoteric graft polymer.
[0023] The reaction principle for preparing amphoteric graft polymers is as follows: In an aqueous system, the hydroxyl groups of hydroxyethyl cellulose generate free radical active sites through a redox initiator, which then graft copolymerize with acrylic acid and diallyl dimethyl ammonium chloride monomers to form polymeric segments with side chains embedded in the cellulose backbone. Sodium hydroxide adjusts the pH of the system to maintain the partially dissociated state of the monomers, thereby affecting the graft polymerization rate and segment distribution. Sodium bisulfite acts as a chain transfer agent to regulate the molecular weight distribution of the polymer, generating a soluble or micro-particulate graft polymer network. Nitrogen protection ensures that the inhibition of free radical polymerization by oxygen in the system is minimized. Finally, the products are separated by precipitation, washing, and drying to obtain a solid polymer with a uniform structure and amphoteric grafted segments for subsequent compound applications.
[0024] Step II: Preparation of epoxy silica-stabilized microparticles Weigh out 160.0 mL of anhydrous ethanol, 45.0 mL of deionized water and 18.0 g of lignin and add them to the reaction vessel. Stir and disperse the mixture. After stirring evenly, add 4.0 mL of 25 wt% ammonia water, then add 16.0 mL of 3-glycidyl etheroxypropyltrimethoxysilane and 18.0 mL of tetraethyl orthosilicate. Heat the reaction vessel to 38 °C and stir for 3.5 h. Then heat it to 48 °C and mature for 7 h. After the reaction is complete, centrifuge and separate the solid. Wash the solid twice with 70 wt% ethanol aqueous solution and once with deionized water. Place the solid in a vacuum drying oven at 55 °C and dry for 8 h. Crush the solid and pass it through an 80-mesh sieve to obtain epoxy silicon stabilized microparticles.
[0025] The reaction principle for preparing epoxy-silicone stabilized microparticles is as follows: Lignin forms dispersed particles in a water / alcohol mixed solvent. The corresponding silane precursor undergoes hydrolysis-condensation under ammonia catalysis to generate a silicon-oxygen network containing epoxy side groups. The water-to-alcohol ratio and temperature control conditions affect the hydrolysis and condensation rate of silane, causing the silicon-oxygen network to deposit and solidify on the surface of lignin particles, forming uniform composite microparticles. In this process, lignin particles provide dispersion support, and silane forms a stable structure through non-covalent bonding with the surface. Centrifugation, washing, and drying remove unreacted substances and solvents, finally obtaining epoxy-silicon stable microparticles with controllable particle size and uniform distribution, providing a solid core material for core-shell composite materials.
[0026] Step III: Preparation of core-shell anti-redeposition agent Weigh out 110.0 mL of deionized water, 25.0 mL of anhydrous ethanol, and 6.0 g of epoxy silicone stabilized microparticles and add them to the reaction vessel. Stir and disperse the mixture. After stirring evenly, add 13.0 g of amphoteric graft polymer and then 1.1 g of sodium carbonate. Heat the reaction vessel to 72 °C and stir for 4.5 h. After the reaction is complete, remove some of the anhydrous ethanol under reduced pressure. Place the obtained material in a vacuum drying oven at 45 °C and dry for 8 h. Crush the material and pass it through a 100-mesh sieve to obtain the core-shell anti-redeposition agent.
[0027] The reaction principle for preparing core-shell anti-redeposition agents is as follows: In a water / alcohol system, epoxy-silica stabilized microparticles act as core particles. Amphoteric grafted polymers adsorb, entangle, and partially coat the particle surface in an ionic environment regulated by sodium carbonate. Temperature control maintains the flexibility and water solubility of the polymer chain segments, which is beneficial for uniform distribution of the shell layer. The desolventizing and drying processes fix the structural morphology of the composite particles, and solid products with controllable particle size are obtained through crushing and sieving. This process does not generate new chemical bonds and is essentially a physical adsorption and composite construction process, forming a stable and dispersible core-shell composite anti-redeposition agent.
[0028] The mechanism of action of core-shell anti-redeposition agents in composite cleaning agents is as follows: The core-shell anti-redeposition agent obtained by this process originates from a hierarchical structure combining an "inorganic particle skeleton and an organic interface layer." Epoxy-silica stabilized microparticles form a relatively stable core support, while amphoteric grafted polymers constitute the outer shell phase, possessing hydrophilic spreading and interface regulation capabilities. This gives the component both particle stability and liquid-phase responsiveness. When introduced into the composite detergent system, it does not primarily perform front-end detergency cleaning, but rather regulates the dispersion, migration path, and re-contact behavior of dirt particles in the washing liquid after they detach from the fabric surface. On one hand, it maintains particle suspension distribution through the hydration and spatial isolation of the shell chain segments; on the other hand, it maintains interface layer stability through the structural support of the core particles, thereby reducing the tendency for particles to re-aggregate and re-attach. Thus, the final product forms a continuous action structure extending from detergency stripping to liquid-phase retention and then to inhibiting redeposition, resulting in more stable performance of the composite detergent in terms of redeposition control, whitening retention, and overall washing synergy. Example
[0029] This embodiment provides a method for preparing a core-shell anti-redeposition agent, including the following steps: Step I: Preparation of amphoteric grafted polymers Weigh out 150.0 mL of deionized water and 14.0 g of hydroxyethyl cellulose and add them to the reaction vessel. Stir until swollen and homogeneous. Add 10.0 mL of acrylic acid, then add 4.0 mL of 50 wt% sodium hydroxide solution and 14.0 mL of 60 wt% diallyl dimethyl ammonium chloride aqueous solution. Continue stirring until homogeneous and then purge with nitrogen gas. Add 9.0 mL of 5 wt% ammonium persulfate aqueous solution and 7.0 mL of 3 wt% sodium bisulfite aqueous solution. Heat the reaction vessel to 68 °C and stir for 5 h. After the reaction is complete, adjust the pH of the system to 7.5 with 10 wt% sodium hydroxide solution. Add three times the volume of anhydrous ethanol to precipitate the mixture. Filter and collect the filter cake. Wash the filter cake three times with 70 wt% ethanol aqueous solution. Place the filter cake in a vacuum drying oven at 55 °C and dry for 12 h. Crush and pass through a 100-mesh sieve to obtain the amphoteric graft polymer.
[0030] Step II: Preparation of epoxy silica-stabilized microparticles Weigh out 200.0 mL of anhydrous ethanol, 65.0 mL of deionized water and 22.0 g of lignin and add them to the reaction vessel. Stir and disperse the mixture. After stirring evenly, add 6.0 mL of 25 wt% ammonia water, then add 20.0 mL of 3-glycidyl etheroxypropyltrimethoxysilane and 22.0 mL of tetraethyl orthosilicate. Heat the reaction vessel to 42 °C and stir for 4.5 h. Then heat it to 52 °C and mature for 9 h. After the reaction is complete, centrifuge and separate the solid. Wash the solid three times with 70 wt% ethanol aqueous solution and twice with deionized water. Place the solid in a vacuum drying oven at 65 °C and dry for 10 h. Crush the solid and pass it through an 80-mesh sieve to obtain epoxy silicon stabilized microparticles.
[0031] Step III: Preparation of core-shell anti-redeposition agent Weigh out 230.0 mL of deionized water, 35.0 mL of anhydrous ethanol, and 9.0 g of epoxy silicone stabilized microparticles and add them to the reaction vessel. Stir and disperse the mixture. After stirring evenly, add 16.0 g of amphoteric graft polymer and then 1.4 g of sodium carbonate. Heat the reaction vessel to 78 °C and stir for 5.5 h. After the reaction is complete, remove some of the anhydrous ethanol under reduced pressure. Place the obtained material in a vacuum drying oven at 55 °C and dry for 10 h. Crush the material and pass it through a 120 mesh sieve to obtain the core-shell anti-redeposition agent. Example
[0032] This embodiment provides a method for preparing a core-shell anti-redeposition agent, including the following steps: Step I: Preparation of amphoteric grafted polymers Weigh out 137.5 mL of deionized water and 12.5 g of hydroxyethyl cellulose and add them to the reaction vessel. Stir until swollen and homogeneous. Add 9.0 mL of acrylic acid, then add 3.5 mL of 50 wt% sodium hydroxide solution and 12.5 mL of 60 wt% diallyl dimethyl ammonium chloride aqueous solution. Continue stirring until homogeneous and then purge with nitrogen gas. Add 8.5 mL of 5 wt% ammonium persulfate aqueous solution and 6.0 mL of 3 wt% sodium bisulfite aqueous solution. Heat the reaction vessel to 66 °C and stir for 5 h. After the reaction is complete, adjust the pH of the system to 7.0 with 10 wt% sodium hydroxide solution. Add three times the volume of anhydrous ethanol to precipitate the mixture. Filter and collect the filter cake. Wash the filter cake three times with 70 wt% ethanol aqueous solution. Place the filter cake in a vacuum drying oven at 50 °C and dry for 11 h. Crush and pass through a 90-mesh sieve to obtain the amphoteric graft polymer.
[0033] Step II: Preparation of epoxy silica-stabilized microparticles Weigh out 180.0 mL of anhydrous ethanol, 55.0 mL of deionized water and 20.0 g of lignin and add them to the reaction vessel. Stir and disperse the mixture. After stirring evenly, add 5.0 mL of 25 wt% ammonia water, then add 18.0 mL of 3-glycidyl etheroxypropyltrimethoxysilane and 20.0 mL of tetraethyl orthosilicate. Heat the reaction vessel to 40 °C and stir for 4.0 h. Then heat it to 50 °C and mature for 8 h. After the reaction is complete, centrifuge and separate the solid. Wash the solid three times with 70 wt% ethanol aqueous solution and twice with deionized water. Place the solid in a vacuum drying oven at 60 °C and dry for 9 h. Crush the solid and pass it through an 80 mesh sieve to obtain epoxy silicon stabilized microparticles.
[0034] Step III: Preparation of core-shell anti-redeposition agent Weigh out 170.0 mL of deionized water, 30.0 mL of anhydrous ethanol, and 7.5 g of epoxy silicone stabilized microparticles and add them to the reaction vessel. Stir and disperse the mixture. After stirring evenly, add 14.5 g of amphoteric graft polymer and then 1.3 g of sodium carbonate. Heat the reaction vessel to 75 °C and stir for 5.0 h. After the reaction is complete, remove some of the anhydrous ethanol under reduced pressure. Place the obtained material in a vacuum drying oven at 50 °C and dry for 9 h. Crush the material through a 110 mesh sieve to obtain the core-shell anti-redeposition agent. Example
[0035] This embodiment provides a method for preparing a composite cleaning agent containing a functional polymeric anti-redeposition agent, including the following steps: Step 1: Preparation of synergistic solubilizer Weigh out 120.0 mL of deionized water and 27.0 g of hydroxypropyl-β-cyclodextrin and add them to the reaction vessel. Stir and dissolve the mixture. After stirring evenly, add 16.0 mL of decyl glucoside and then 13.0 g of sodium gluconate. Heat the reaction vessel to 40 °C and stir for 1 h. After the reaction is complete, concentrate the mixture under reduced pressure to a solid content of 65 wt%. Place the concentrate in a vacuum drying oven at 40 °C and dry for 8 h. Pulverize the concentrate and pass it through an 80-mesh sieve to obtain a synergistic solubilizer.
[0036] The reaction principle for preparing synergistic solubilizers is as follows: Hydroxypropyl-β-cyclodextrin dissolves in water to form a cavity structure. Decyl glucoside is embedded in the cyclodextrin cavity through non-covalent interactions or forms dynamic intermolecular interactions with it. At the same time, sodium gluconate regulates the ionic environment and solvation conditions of the system. Temperature control and stirring ensure uniform dispersion of each component. Vacuum concentration enables solid content control and facilitates drying into solid powder. No new covalent bonds are formed in the system. Each component forms a stable compound structure in a non-covalent manner, providing a uniformly dispersible solubilizing system for composite detergents.
[0037] The mechanism of action of synergistic solubilizers in composite cleaning agents is as follows: The synergistic solubilizer obtained by this process originates from an ordered dispersion structure formed by the non-covalent compounding of multiple components. Hydroxypropyl-β-cyclodextrin provides a cavity carrier with inclusion function, decyl glucoside provides surface activity and interfacial affinity, and sodium gluconate endows the system with a relatively stable solubilization environment and ion regulation ability. This component has composite properties such as molecular inclusion, interfacial transition and aqueous phase dispersion. After entering the composite detergent system, it can improve the dispersion uniformity of hydrophobic active substances in the aqueous phase, improve the compatibility between different functional components, and reduce the tendency of local aggregation or precipitation. On the other hand, it can form a smoother transfer interface on the fabric surface, between dirt particles and detergent liquid, so that the release, migration and spread of active components are more continuous. Thus, the final product changes from the instantaneous action dominated by a single detergency component to a composite action system with front-end solubilization and dispersion and subsequent interfacial synergistic characteristics, showing a more stable performance tendency in terms of detergency efficiency, system stability, solubility and dispersibility and overall washing coordination.
[0038] Step 2: Preparation of composite cleaning agent By weight, weigh 170.0 parts sodium dodecylbenzenesulfonate, 110.0 parts trisodium citrate dihydrate, 70.0 parts sodium carbonate and 4.0 parts sodium benzoate and add them to a mixer for premixing. After stirring evenly, add 32.0 parts of the synergistic solubilizer prepared in step one, and then add 23.0 parts of the core-shell anti-redeposition agent prepared in Example 1. Continue stirring and mixing. After mixing, granulate through a 40-mesh sieve, seal and package to obtain the composite cleaning agent.
[0039] The reaction principle for preparing composite cleaning agents is as follows: Surfactants, alkaline salts, and preservatives are uniformly dispersed under solid conditions. Polymer synergistic solubilizers and core-shell anti-redeposition agents are mixed in in particulate form. Mechanical stirring ensures uniform distribution of each component. Granulation and sieving processes control particle size consistency and eliminate agglomeration or large particles. The entire process does not involve chemical reactions. The system exists in a solid compound form, and each component maintains its original structure and proportion, achieving a composite cleaning agent product with uniform distribution and controllable particle morphology. Example
[0040] This embodiment provides a method for preparing a composite cleaning agent containing a functional polymeric anti-redeposition agent, including the following steps: Step 1: Preparation of synergistic solubilizer Weigh out 150.0 mL of deionized water and 33.0 g of hydroxypropyl-β-cyclodextrin and add them to the reaction vessel. Stir and dissolve the mixture. After stirring evenly, add 20.0 mL of decyl glucoside and then 17.0 g of sodium gluconate. Heat the reaction vessel to 50°C and stir for 2 hours. After the reaction is complete, concentrate the mixture under reduced pressure to a solid content of 75 wt%. Place the concentrate in a vacuum drying oven at 50°C and dry for 10 hours. Pulverize the concentrate and pass it through a 100-mesh sieve to obtain a synergistic solubilizer.
[0041] Step 2: Preparation of composite cleaning agent By weight, weigh 190.0 parts sodium dodecylbenzenesulfonate, 130.0 parts trisodium citrate dihydrate, 90.0 parts sodium carbonate and 6.0 parts sodium benzoate and add them to a mixer for premixing. After stirring evenly, add 38.0 parts of the synergistic solubilizer prepared in step one, and then add 27.0 parts of the core-shell anti-redeposition agent prepared in Example 2. Continue stirring and mixing. After mixing, granulate through a 60-mesh sieve, seal and package to obtain the composite cleaning agent. Example
[0042] This embodiment provides a method for preparing a composite cleaning agent containing a functional polymeric anti-redeposition agent, including the following steps: Step 1: Preparation of synergistic solubilizer Weigh out 135.0 mL of deionized water and 30.0 g of hydroxypropyl-β-cyclodextrin and add them to the reaction vessel. Stir and dissolve the mixture. After stirring evenly, add 18.0 mL of decyl glucoside and then 15.0 g of sodium gluconate. Heat the reaction vessel to 45°C and stir for 2 hours. After the reaction is complete, concentrate the mixture under reduced pressure to a solid content of 70 wt%. Place the concentrate in a vacuum drying oven at 45°C and dry for 9 hours. Pulverize the concentrate and pass it through a 90-mesh sieve to obtain a synergistic solubilizer.
[0043] Step 2: Preparation of composite cleaning agent Weigh out 180.0 parts by weight of sodium dodecylbenzenesulfonate, 120.0 parts by weight of trisodium citrate dihydrate, 80.0 parts by weight of sodium carbonate and 5.0 parts by weight of sodium benzoate and add them to a mixer for premixing. After stirring evenly, add 35.0 parts by weight of the synergistic solubilizer prepared in step one, and then add 25.0 parts by weight of the core-shell anti-redeposition agent prepared in Example 3. Continue stirring and mixing. After mixing, granulate through a 50-mesh sieve, seal and package to obtain the composite cleaning agent.
[0044] Comparative Example 1 The difference between this comparative example and Example 6 is that anhydrous sodium sulfate is used in step two to replace the synergistic solubilizer in an equal amount.
[0045] Comparative Example 2 The difference between this comparative example and Example 6 is that anhydrous sodium sulfate is used in step two to replace the core-shell anti-redeposition agent in an equal amount.
[0046] Comparative Example 3 The difference between this comparative example and Example 6 is that sodium carbonate was omitted during the preparation of the core-shell anti-redeposition agent used in step two.
[0047] Performance testing: The samples used for all performance tests in this scheme are the composite cleaning agents prepared in Examples 4-6 and Comparative Examples 1-3. Unless otherwise specified, all tests are conducted at 23±2℃ and 50±5% relative humidity. The composite cleaning agents used in each test are prepared into test solutions according to the corresponding methods before measurement.
[0048] The detergency performance was tested according to GB / T 4287-2017 "Textiles - Tests for Color Fastness - Determination of Detergency Performance of Detergents". The test results are expressed as detergency rate, in % (%). The specific test method is as follows: Weigh 0.400g of compound detergent and add it to 200mL of deionized water. Stir at 100rpm for 10min to prepare a test solution with a mass concentration of 2.0g / L. Select standard stained cotton cloths with grease, soy sauce and coffee stains as test objects. Wash at 40℃ for 30min with a stirring speed of 100rpm. After washing, rinse with deionized water and air dry. Use a spectrophotometer to measure the change in reflectance of the stained area before and after washing, and calculate the stain removal rate according to the standard method. Five measuring points are selected in the effective test area for each sample.
[0049] The whitening performance was tested according to GB / T 8408-2008 "Instrumental Determination of Whiteness of Textiles", and the test results were expressed as whitening index, with the unit being dimensionless. The specific test method is as follows: Weigh 0.400g of compound detergent and add it to 200mL of deionized water. Stir at 100rpm for 10min to prepare a test solution with a mass concentration of 2.0g / L. Select a white cotton cloth standard test piece as the test object, wash it at 40℃ for 30min with a stirring speed of 100rpm. After washing, rinse with deionized water and air dry. Use a colorimeter to measure the change of L* value before and after washing, and calculate the whitening index according to the standard method.
[0050] The anti-redeposition performance was tested according to GB / T 18401-2010 "Textiles - Determination of Anti-redeposition Performance of Household Detergents". The test results are expressed as the redeposition rate, in percentage (%). The specific test method is as follows: Weigh 0.400g of compound cleaning agent and add it to 200mL of deionized water. Stir at 100rpm for 10min to prepare a test solution with a mass concentration of 2.0g / L. Wash the stained cloth and the clean white cloth at the same time. Wash at 40℃ for 30min with a stirring speed of 100rpm. After washing, take out the clean white cloth, rinse it with deionized water and dry it. Measure the increase in ash content and calculate the redeposition rate according to the standard method.
[0051] Suspension stability was tested according to QB / T 2767-2011 "Test Method for Stability of Detergents", and the test results were expressed as turbidity in NTU. The specific test method is as follows: Weigh 1.000g of compound cleaning agent and add it to 99.000g of deionized water. Stir at 100rpm for 10min to prepare a test solution with a mass fraction of 1.0wt%. Let it stand at 25℃ for 24h. After standing, use the turbidimetric method to determine the turbidity and observe whether there is stratification, sedimentation or flocculation in the system to evaluate its dispersion stability.
[0052] The dissolution rate was determined according to the solubility test method in QB / T 2767-2011 "Test Methods for Stability of Detergents". The test result is expressed as the dissolution rate, with units of g·min. -1 ; The specific test method is as follows: Weigh 5.00g of compound cleaning agent and add it to 200mL of deionized water. Under the condition of stirring at 100rpm, record the time required from the addition of the sample to the point where there are no visible particles in the system and the dispersion is uniform. Calculate the dissolution rate. The specific data are shown in Table 1. Table 1 - Performance Test Data for Each Sample
[0053] Data Analysis: Comparative analysis of the data in Table 1 reveals that the composite detergent prepared in this invention, when configured as an aqueous solution with a mass concentration of 2.0 g / L, exhibits a detergency of 89.7%, a whitening index of 2.9, a redeposition rate of 4.0%, a turbidity of 59 NTU, and a dissolution rate of 1.19 g·min⁻¹. -1 All data points are better than the comparative data, indicating that: In Comparative Example 1, under the condition of lack of synergistic solubilizer, the system lost the dispersion and hydration channels formed by hydroxypropyl-β-cyclodextrin, decyl glucoside and sodium gluconate, and the release and migration rhythm of active components in the liquid phase could not be kept balanced; the synchronous interaction between sodium dodecylbenzenesulfonate and other components in the liquid phase was interrupted, the continuity of contact between the fiber surface and dirt particles decreased, the connection between the initial dispersion and subsequent action stages of the system was weakened, the component cooperation chain was broken, resulting in a decrease in the overall composite effect, indicating the core role of synergistic solubilizer in the coordination of the system.
[0054] In Comparative Example 2, in the system lacking a core-shell anti-redeposition agent, after the particles detached from the fiber surface, they lost their structure retention and liquid phase constraint, resulting in an unbalanced particle distribution. The connection between the preceding and following stages of the action was interrupted. Although the surface-active components completed the initial cleaning, the continuity of particle migration and suspension in the liquid phase was disrupted, the uniformity of contact between the fiber and the particles decreased, the overall coordination of the system was reduced, and the performance of the composite action was weakened. This shows the key synergistic role of the core-shell structure in maintaining particle distribution and the synchronous action of multiple components.
[0055] In Comparative Example 3, under the condition of physical blending rather than core-shell composite, the amphoteric graft polymer and the epoxy-silica stabilized microparticles lose the interfacial coupling mechanism, and the particles cannot form a synchronous response in the liquid phase; the component action rhythm shows local deviation, the continuous protection of liquid phase particles and the balanced state of fiber coverage are weakened, the transition from initial dispersion to subsequent action of the system is interrupted, the cooperative chain is missing, the continuity of cleaning action decreases, and the composite effect is lower than that of the structured composite system, highlighting the unique value of core-shell composite in multi-component synergy.
[0056] Ultimately, it is demonstrated that the system does not linearly superimpose the surface-active components, dispersion components, and composite carrier. Instead, it forms a sequential operational relationship in continuous stages such as aqueous phase migration, interfacial spreading, particle detachment, and subsequent liquid phase maintenance. Among these, the synergistic solubilization configuration affects the release rhythm and distribution uniformity of the active components, while the core-shell composite relationship further influences the existence state of particles in the liquid phase and the probability of re-contact with the fiber interface. When relevant configurations are replaced, removed, or simply coexisted, the continuity of transmission between the various action stages within the system weakens, and the interfacial response and liquid phase maintenance become difficult to maintain synchronously. Thus, the material composition and the operational process exhibit a significant coupling characteristic, and its effect cannot be fully explained by isolated component changes.
[0057] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A composite cleaning agent containing a functional polymeric anti-redeposition agent, characterized in that, The raw material composition includes the following parts by weight: 170-190 parts sodium dodecylbenzenesulfonate, 110-130 parts trisodium citrate dihydrate, 70-90 parts sodium carbonate, 4-6 parts sodium benzoate, 32-38 parts synergistic solubilizer and 23-27 parts core-shell anti-redeposition agent; The synergistic solubilizer is a complex polymer dispersion composed of cyclodextrin, alkyl glycoside and polycarboxylate; The core-shell anti-redeposition agent is a core-shell type functional polymer dispersion composed of an epoxy-siloxane lignin hybrid core and a hydroxyethyl cellulose-grafted amphoteric polycarboxylate shell.
2. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 1, characterized in that, The preparation method of the core-shell anti-redeposition agent is as follows: deionized water, anhydrous ethanol and epoxy silicon stabilized microparticles are added to a reaction vessel and stirred and dispersed. After stirring evenly, amphoteric graft polymer is added, followed by sodium carbonate. The reaction vessel is heated to 72-78℃ and stirred for 4.5-5.5 hours. The core-shell anti-redeposition agent is then obtained through post-treatment.
3. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 2, characterized in that, The ratio of deionized water, anhydrous ethanol, epoxy silicone stabilized microparticles, amphoteric graft polymer and sodium carbonate is 110-230mL:25-35mL:6-9g:13-16g:1.1-1.4g.
4. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 2, characterized in that, The preparation method of the amphoteric graft polymer is as follows: Deionized water and hydroxyethyl cellulose are added to a reaction vessel and stirred to swell. After stirring evenly, acrylic acid is added, followed by 50wt% sodium hydroxide solution and 60wt% diallyl dimethyl ammonium chloride aqueous solution. After stirring evenly, nitrogen gas is introduced, followed by 5wt% ammonium persulfate aqueous solution and 3wt% sodium bisulfite aqueous solution. The reaction vessel is heated to 63-68℃ and stirred for 4-5 hours. The amphoteric graft polymer is obtained after post-treatment.
5. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 4, characterized in that, The ratio of deionized water, hydroxyethyl cellulose, acrylic acid, 50wt% sodium hydroxide solution, 60wt% diallyl dimethyl ammonium chloride aqueous solution, 5wt% ammonium persulfate aqueous solution, and 3wt% sodium bisulfite aqueous solution is 125-150mL:11-14g:8-10mL:3-4mL:11-14mL:8-9mL:5-7mL.
6. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 2, characterized in that, The preparation method of the epoxy-silicone stabilized microparticles is as follows: anhydrous ethanol, deionized water and lignin are added to a reaction vessel and stirred and dispersed. After stirring evenly, 25wt% ammonia water is added, followed by 3-glycidoxypropyltrimethoxysilane and tetraethyl orthosilicate. The reaction vessel is heated to 38-42℃ and stirred for 3.5-4.5h. Then, the temperature is raised to 48-52℃ and matured for 7-9h. The epoxy-silicone stabilized microparticles are obtained by post-treatment. The ratio of the amount of anhydrous ethanol, deionized water, lignin, 25wt% ammonia water, 3-glycidoxypropyltrimethoxysilane and tetraethyl orthosilicate is 160-200mL:45-65mL:18-22g:4-6mL:16-20mL:18-22mL.
7. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 1, characterized in that, The preparation method of the synergistic solubilizer is as follows: deionized water and hydroxypropyl-β-cyclodextrin are added to a reaction vessel and stirred to dissolve. After stirring evenly, decyl glucoside is added, followed by sodium gluconate. The reaction vessel is heated to 40-50℃ and stirred for 1-2 hours. The synergistic solubilizer is then obtained through post-treatment.
8. The composite cleaning agent containing a functional polymeric anti-redeposition agent according to claim 7, characterized in that, The ratio of deionized water, hydroxypropyl-β-cyclodextrin, decyl glucoside, and sodium gluconate is 120-150 mL: 27-33 g: 16-20 mL: 13-17 g.
9. The method for preparing the composite cleaning agent containing a functional polymeric anti-redeposition agent as described in any one of claims 1-8, characterized in that, Includes the following steps: Sodium dodecylbenzenesulfonate, trisodium citrate dihydrate, sodium carbonate, and sodium benzoate were added to a mixer for premixing, followed by post-processing to obtain a composite cleaning agent.